The Urgency of Islamic Education Based in Multiculturalism in Educational Institutions - M.Jamaludin; Jasiah (International Journal of Community Engagement Payungi, 2025)
The purpose of this article is to analyze and explore the urgency of implementing multicultural Islamic religious education management in Indonesia to create an inclusive and harmonious educational environment. The method used in this research is library research where the author uses a descriptive normative research approach with more emphasis on the strength of data analysis on existing data sources. What is meant by literature study is all efforts made by researchers to collect information relevant to the topic or problem that will be or is being studied. The information can be obtained from scientific books, research reports, scientific papers, theses, dissertations, regulations, provisions, yearbooks, encyclopedias, and other written sources both printed and electronic. Library research, by analyzing literature and policies related to multicultural Islamic religious education management. The results of the study indicate that the integration of multicultural values in the Islamic religious education curriculum can increase understanding and appreciation of cultural and religious diversity, as well as strengthen national unity. The urgency of multicultural Islamic religious education management in Indonesia is: 1). As an alternative means of conflict resolution, 2). To prevent students from being uprooted from their cultural roots, 3) As a foundation for developing the National Curriculum. The implications of this research emphasize the need for educational policies that support the implementation of multicultural Islamic religious education management and strengthen the capacity of teachers as agents of change in implementing multicultural principles in the classroom.